Relational inclusivity in the elementary classroom : a teacher's guide to supporting student friendships and building nurturing communities - Mamas, Christoforos; Cohen, Shana, 1966-; Holtzman, Caren (New York : Routledge, 2024)
"Learn how to support and encourage the development of strong, nurturing relationships among your students of all neurotypes and needs ranges with this practical, field-tested guide. Featuring classroom lessons, group activities, and a toolkit for creating a social network map specific to your classroom, this book shows teachers how to easily implement inclusive practices into their daily routines. The book is centered on a 'research-integrated' model and demonstrates how teachers can use simple tools to gather real-time information on the social networks and student relationships to guide them in better organizing student groupings and planning classroom activities. Moving beyond transactional approaches like behavioral regulation and rule setting, the book prioritizes relationship building as vital to building inclusive classroom communities. It is key reading for in-service educators striving to create the kind of learning environment that meets the socio-emotional needs of all learners. Pre-service educators, educational researchers and administrators will also benefit from this helpful resource"--
Chapter 1: The case for relational inclusivity -- Chapter 2: Research practice partnerships in classrooms -- Chapter 3: The social network analysis toolkit -- Chapter 4: Who are your friends? -- Chapter 5: Who do you play with at recess? -- Chapter 6: Who do you go to for help with your classwork? -- Chapter 7: Who do you talk to if you are having a bad day? -- Chapter 8: Moving forward.
Keywords: Inclusive education -- United States -- Handbooks, manuals, etc; Children with disabilities -- Education (Elementary) -- United States; Teaching -- Aids and devices -- Handbooks, manuals, etc; Teacher-student relationships -- United States; EDUCATION / Elementary